A Critical Survey of Dithiocarbamate Reversible Addition‐Fragmentation Chain Transfer (RAFT) Agents in Radical Polymerization. Issue 3 (14th September 2018) - Moad, Graeme
ABSTRACT: This article provides a critical review of the properties, synthesis, and applications of dithiocarbamates Z′Z″NC(=S)SR as mediators in reversible addition‐fragmentation chain transfer (RAFT) polymerization. These are among the most versatile RAFT agents. Through choice of substituents on nitrogen (Z′, Z″), the polymerization of most monomer types can be controlled to provide living characteristics (i.e., low dispersities, high end‐group fidelity, and access to complex architectures). These include the more activated monomers (MAMs; e.g., styrenes and acrylates) and the less activated monomers (LAMs; e.g., vinyl esters and vinylamides). Dithiocarbamates with balanced activity (e.g., 1 H ‐pyrazole‐1‐carbodithioates) or switchable RAFT agents [e.g., a N ‐methyl‐ N ‐(4‐pyridinyl)dithiocarbamate] allow control MAMs and LAMs with a single RAFT agent and provide a pathway to low‐dispersity poly(MAM)‐ block ‐poly(LAM). © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2019, 57, 216–227 Abstract : The properties, synthesis, and applications of dithiocarbamates Z′Z″NC(=S)SR as mediators in reversible addition‐fragmentation chain transfer (RAFT) polymerization are reviewed. Through choice of substituents on nitrogen (Z′, Z″), the polymerization of both more activated monomers (MAMs; e.g., acrylates, acrylamides, acrylonitrile, and styrenes) and less activated monomers (LAMs, e.g., vinyl halides, vinyl esters, and vinylamides) can be controlled to provide living characteristics (i.e., low dispersities, high end‐group fidelity, and access to complex architectures).